PERANCANGAN STRUKTUR BETON BERTULANG RUMAH SUSUN ATLET PONTANAK 6 LANTAI: PERANCANGAN STRUKTUR BETON BERTULANG RUMAH SUSUN ATLET PONTANAK 6 LANTAI - Maulida-Akbar, Hasri-alief Bryantama; rasiwan, rasiwan; supardi, iwan (RETENSI, 2021)
The increasing population growth, especially in West Kalimantan, is still making efforts to equalize developmentto meet housing needs by seeking land availability by building infrastructure in the form of vertical buildings,namely flats. The construction of flats supports the needs of athletes or sports participants that function astemporary residences in order to maintain the athletes' concentration, mental and physical well-being. In thebuilding there is a structure of beams, columns, foundations, floor plates and roofs. In designing the structure, itis planned to be strong enough to withstand the forces that may occur according to the load calculation, both inthe form of vertical and horizontal forces, in designing the reinforced concrete structure of an athlete's flat whichconsists of 6 floors using a roof and concrete quality (fc'). 35 MPa and steel quality (fy) 420 MPa which iscalculated based on the Indonesian National Standard (SNI), namely SNI 03-2847-2013 because the use of SNI03-2847-2013 can meet the calculations carried out in this study and SNI 1726-2019, as well as using theSAP2000 application for force calculations - style inside. So that the plan drawing can be made according to thecalculation results obtained. From the calculation results obtained reinforcement for the floor slab structure witha thickness of 140 mm using field reinforcement and support reinforcement D10-175. The beams used are 400mm × 600 mm, 350 mm × 600 mm and 300 × 400 mm, with D19 main reinforcement and 10 mm beugelreinforcement. The column used is 500 mm × 500 mm with reinforcement using longitudinal reinforcementmeasuring D25 and 10 mm begel reinforcement. The foundation used is a pile foundation, with a pile size of 300mm × 300 mm and a pile cap of 2100 mm × 1350 mm × 750 mm with principal reinforcement D22-150 and D12-150.